A Voltammetric Electronic Tongue Based on Commercial Screen‐printed Electrodes for the Analysis of Aminothiols by Differential Pulse Voltammetry. Issue 6 (8th March 2017) - Pérez‐Ràfols, Clara; Gómez, Ana; Serrano, Núria; Díaz‐Cruz, José Manuel; Ariño, Cristina; Esteban, Miquel
Abstract: A voltammetric electronic tongue has been designed as a proof of concept for the analysis of aminothiols by differential pulse voltammetry and has been tested in ternary mixtures of cysteine (Cys), homocysteine (hCys) and glutathione (GSH). It consists of three screen‐printed electrodes of carbon, carbon nanofibers and gold cured at low temperature. A preliminary calibration study carried out separately for each aminothiol confirmed that, working at an optimal pH value of 7.4, every electrode produces differentiated responses for every analyte (cross‐response). As for the tongue, it was applied to calibration and validation mixtures of Cys, hCys and GSH and provided voltammograms that, baseline‐corrected, normalized and combined in different ways were submitted to partial least squares (PLS) calibration. The calibration models produced good predictions of the concentrations of all three analytes, which suggest that the proposed voltammetric tongue improves the performance of a previous design based on linear sweep voltammetric measurements under acidic conditions. Abstract :